Quality of life of women working from home in COVID-19 lockdown: a questionnaire survey - Raju, Suruthi; Kumar, Vijay Krishna (International Journal Of Community Medicine And Public Health, 2020)
Background: Lockdown as a precaution is aimed to reduce the community transmission and to defeat the pandemic COVID-19. The pandemic lockdown has an impact on lifestyle strategies in work from home employees. Methods: A cross sectional, questionnaire study with observational sampling of size no. 110 was conducted through web based data collection (google form) across India. Results: Data shows lockdown impact on lifestyle strategies like physical health, psychological health, social relationship and environmental factors of working from home employees were found significant. Majority of participants (working from home women) showed better quality of life in lockdown. Conclusions: This web-based survey shows significant results to highlight that women can balance their life style strategies with daily routine in COVID-19 pandemic lockdown. Lockdown situation made women more active, mobile and balance their official work along with the family setup. 67.3% respondents were married and working from home and 48% of participants maintaining their better quality of life since lockdown.